Education and practice gaps on atrial fibrillation and anticoagulation: a survey of cardiovascular nurses. Issue 1 (December 2016) - Ferguson, Caleb; Inglis, Sally; Newton, Phillip; Middleton, Sandy; Macdonald, Peter; Davidson, Patricia
Abstract Background Patients' knowledge of their atrial fibrillation (AF) and anticoagulation therapy are determinants of the efficacy of thromboprophylaxis. Nurses may be well placed to provide counselling and education to patients on all aspects of anticoagulation, including self-management. It is important that nurses are well informed to provide optimal education to patients. Current practice and knowledge of cardiovascular nurses on AF and anticoagulation in the Australian and New Zealand (ANZ) context is not well reported. This study aimed to; 1) Explore the nurse's role in clinical decision making in anticoagulation in the setting of AF; 2) Describe perceived barriers and enablers to anticoagulation in AF; 3) Investigate practice patterns in the management of anticoagulation in the ANZ setting; 4) Assess cardiovascular nurses' knowledge of anticoagulation. Methods A paper-based survey on current practices and knowledge of AF and anticoagulation was distributed during the Australian Cardiovascular Nursing College (ACNC) Annual Scientific Meeting, February 2014. This survey was also emailed to Cardiovascular Trials Nurses throughout New South Wales, Australia and nursing members of the Cardiac Society of Australia and New Zealand (CSANZ). Results There were 41/73 (56 %) respondents to the paper-based survey. A further 14 surveys were completed online via nurse members of the CSANZ, and via an investigator developed NSW cardiovascular trials nurse email distribution list. A total of 55 surveys were completed and included in analyses. Prior education levels on AF, stroke risk, anticoagulation and health behaviour modification were mixed. The CHA2 DS2 VASc and HAS-BLED risk stratification tools were reported to be underused by this group of clinicians. Reported key barriers to anticoagulation included; fears of patients falling, fears of poor adherence to medication taking and routine monitoring. Patient self-monitoring and self-management were reported as underutilised. ANZ cardiovascular nurses reported their key role to be counselling and advising patients on therapy regimens. Anticoagulant-drug interaction knowledge was generally poor. Conclusion This study identified poor knowledge and practice in the areas of AF and anticoagulation. There is scope for improvement for cardiovascular nurses in ANZ in relation to AF and anticoagulation knowledge and practice.